2016 Calculus Contest Solutions
2016 Calculus Contest Solutions
2016 Calculus Contest Solutions
(D) 4 (E) 5
I
g (n) (x)( =) (−1)n n![x−(n+1) − (x − 1)−(n+1) ] for every n natural number. In particular,
g (2016) 21 = (2016!)(22017 + 22017 ) = (2016!)22018 which implies that α = 2. This gives
B as the correct answer.
If h = f ◦ f , what is h′ (0)?
5. The function G(x) = (x2 + m)ex , defined for all real values of x and m a fixed real
valued constant, has two distinct inflection points if and only if m < a. What is the
value of a ?
Solution: We calculate the second derivative and obtain G′′ (x) = (x2 + m + 4x + 2)ex .
In order to have two distinct inflection points, we need have two distinct real solutions
of the quadratic x2 + 4x + m + 2 = 0. It is then equivalent to requiring that its
determinant ∆ = 16 − 4(m + 2) = 8 − 4m > 0 or m < 2. So, the answer is B .
x+1
6. The function g(x) = defined on the whole real line, has a maximum value of
x2 + 8
g(a) and a minimum value of g(b). Then, what is the value of (a − b)/2 ?
II
What is m?
Solution: The limit is equivalent to limx→0 cot x ln |cos x + sin 2x + sin 3x| = m. Us-
ing L’Hospital’s Rule, we have
8. If for all real x we define f (x) = 6x5 − 15x4 + 10x3 , then the inverse of f , f −1 , exists
and it is differentiable. The derivative of the inverse function at 1/2 is a rational
number, i.e.,
1 d −1 1 m
(f −1 )′ ( ) = (f )( ) = ,
2 dx 2 n
which is written in reduced form using two natural numbers m, n ∈ N. What is 2m−n?
Solution: If we denote by α the angle in the first quadrant, such that sin α = √2 . It
5
follows that cos α = √15 . with this notation we can change the inequality to
k k
(sin x cos α − sin α cos x)2 ≤ ⇔ sin(x − α)2 ≤ .
5 5
III
This shows that k = 5, which makes E the correct answer.
(D) 4 (E) 5
Solution: Using L’Hospital’s Rule we get that lim k(x) = limx→0 2e2x = 2 which
x↗0
means that b = 2. Similarly, lim k(x) = limx→1 (1/x) = 1, which means a + b = 1 and
x↘1
so a = −1. Therefore the answer is C .
(D) 4 (E) 5
Solution: First, we calculate the derivative f ′ (x) = (4 − x)(x − 1)2 e−x and then the
′′ −x 2 ′′
√ f (x) = e (x − 8x + 13)(x − 1). Solving for f (x) = 0 gives x1 = 1
second derivative
and x2,3 = 4 ± 3. Hence, the answer is A .
IV
12. The cubic of equation y = h(x) = x + 2x3
is shown in the figure on the right,
together with its tangent line at the
point (− 43 , h(− 34 )). This tangent line
intersects the cubic at another point:
(mn
, h( m
n
)), where m and n are relatively
prime natural numbers. Find 2m − n.
(D) 4 (E) 5
for any point a. So, if we want to solve the equation h(x) = h(a) + h′ (a)(x − a), we
obtain equivalently, x = a a double root, and the equation 3c0 a + c1 + c0 (x − a) = 0 or
x = −2a − cc01 . So, in our particular case the tangent line intersects the curve y = h(x)
again at ( 32 , h( 32 )). Thus, 2m − n = 4 and so the correct answer is D .
(D) 4 (E) 5
Solution: We need to see where the two graphs intersect: cos x = 1 + cos 2x or using
one of the double angle formulas, this is equivalent to cos x = 2 cos2 x. So, we get
cos x = 0 or cos x = 1/2. Thus, we need to integrate between π/3 and π/2. Hence,
∫ π/2
A = π/3 (cos x − 1 − cos 2x)dx which implies
V
π/2 π/2 sin 2x π/2 1√ π
A = sin x|π/3 − x|π/3 − |π/3 = 1 − 3− .
2 4 6
This shows that D is the correct answer.
(D) 4 (E) 5
Solution: Assuming that the line of equation y = mx+n is tangent to both parabolas,
it means that the polynomials x2 − 6x + 10 − mx − n = x2 − (m + 6)x + 10 − n and
2x2 + 6x − 4 + mx + n = 2x2 + (6 + m)x + n − 4 are both perfect squares. This is
equivalent to (m + 6)2 − 4(10 − n) = (6 + m)2 − 4(2)(n − 4) = 0. This system gives
n = 6 and m1 = −2 or m2 = −10. Hence the answer is E .
15. The nonzero function E satisfies the differential equation E ′ (t) = E(t)2016 for every t
real number and the initial conditions E(0) = 1. If
E(−1)−2015 = 2015 + α
what is the value of α?
VI
Solution: Using the Fundamental Theorem of Calculus we get
1 1
F ′ (x) = 2
2 sec2 2x − sec2 x,
(1 + tan 2x) 2 (1 + tan2 x)2
or,
17. The recurrent sequence {xn } satisfies the recurrence xn+1 = 2xn (1−xn ) for every n ≥ 1
and x1 = 1/2016. Knowing that {xn } is convergent to L, what is L−1 ?
18. We define f by the rule f (x) = (sin x)6 + (cos x)6 for all real numbers x. Knowing that
c is the smallest positive number with the property
∫ 2π
1
f (c) = f (x)dx
2π 0
find πc .
f (x) = (sin2 x)3 + (cos2 x)3 = sin4 x − sin2 x cos2 x + cos4 x = 1 − 3 sin2 x cos2 x, ⇔
3 2 3 5 3
f (x) = 1 − sin 2x = 1 − (1 − cos 4x) = + cos 4x.
4 8 8 8
∫ 2π
So, 0 f (x)dx = 58 (2π). Then the given equation in c is equivalent to cos(4c) = 0. The
smallest positive solution of this equation is clearly given by 4c = π/2, which attracts
π/c = 8. Hence, C is the answer.
VII
19. [∗2 ] We denote by L the following limit:
1 ∑ 2 k
n
L = lim 3 k en .
n→∞ n
k=1
Find e − L.
Solution: We use the Riemann Sums definition ∫ 2 of the definite integral for f (x) = x2 ex
on the interval (0, 1]. We can compute easily 0 f (x)dx = e (x − 2x + 2)|10 = e − 2.
x 2
Hence
1 ∑ k2 k
n
lim 2
e n = e − 2.
n→∞ n n
k=1
Solution: We think of a point (x, y(x)) on the curve x2 + 6xy + 4y 2 = 25, and as
a function of x we need to minimize 2x2 + y(x)2 . Hence we look for critical points,
or 4x + 2yy ′ = 0. This implies y ′ = −2x/y. Using implicit differentiation we get
2x + 6y + 6xy ′ + 8yy ′ = 0 or 6x2 + 7xy − 3y 2 = 0. This homogeneous equation can be
solved by factorization (2x + 3y)(3x − y) = 0. Then y = 3x or y = −2x/3.
5
First, we look at y = 3x: x2 + 6x(3x) + 4(9x2 ) = 25 or x2 = 11
. This gives 2x2 + y 2 =
10
11
+ 9(5)
11
= 5.
The other case gives no intersection with the curve. The curve is a hyperbola ((x +
3y)2 − 5y 2 = 25) and so 2x2 + y 2 can be as large as we want. Therefore, the minimum
is 5 and E is the correct answer.
VIII